Niger : First Review under the Three-Year Poverty Reduction and Growth Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
Despite the difficulties of Niger's circumstances, it showed satisfactory performance under the Poverty Reduction and Growth Facility (PRGF) Arrangement. However, a weakening in program implementation and a reassessment of priorities of the program led to slippages. Executive Directors advised the authorities to implement prudent policies in the revised program to avoid financial slippages. The authorities have shown a strong commitment in the preparation of the full Poverty Reduction Strategy Paper. Directors agreed that Niger has completed the first review under the PRGF Arrangement, and granted waivers.